High-chain fatty acid esters of 1-hexadecanol for low temperature thermal energy storage with phase change materials - (:unkn) unknown (ELSEVIER SCIENCE BV, 2012)
High-chain fatty acid esters of higher alcohols have recently been investigated as novel organic phase change materials (PCM) for thermal energy storage. A series of high-chain fatty acid esters of 1-hexadecanol (cetyl alcohol) were prepared through esterification reaction between 1-hexadecanol and C10-C20 fatty acids with even carbon number in the absence of catalyst and under vacuum. FT-IR spectrometer, differential scanning calorimeter (DSC) and thermo-gravimetric analyzer (TGA) were intensively used for chemical and thermal analyses. Phase change temperature, enthalpy, specific heat (C-p), thermal decomposition and reliability after 1000 thermal cycles were obtained with necessary statistical data to clarify the thermal properties of the materials. The DSC analyses indicated that the melting temperatures of the high-chain fatty acid esters of cetyl alcohol were between 29 degrees C and 60 degrees C with phase change enthalpy above 185 kJ/kg. The results showed that these materials were favorable for low temperature heat transfer applications with superior thermal properties and reliability. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Phase change materials; Thermal energy storage; PCM; Fatty acid ester; Cetyl; heat deposition; LATENT-HEAT STORAGE; SOLAR COLLECTOR; PCM; PERFORMANCE; SYSTEM